IMPLEMENTASI APLIKASI PEMESANAN BARANG DAN DATA PIUTANG PADA PT. WORLD INNOVATIVE TELECOMUNICATION BANJARMASIN - Auliya Rahman; Ibrahim Ibrahim (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
Implementation of information systems in various fields is a must, because it is people who prioritize faster and more accurate problem solving. Distributors who are engaged in the distribution of national-scale opposition phones desperately need a data system that can be computerized well. All things related to ordering goods so far using semi-computer technology such as Ms Word and Ms Excel, but only limited data processing and reporting, not all using a system specifically for ordering and processing of data receivable at the company so that slow down the report or information needed. The method used in making this system is the observation and documentation starting from the collection of existing data, problem analysis, system design until implementation. The system created using the application Borland Delphi 7.0 and MySql for processing goods and ordering data made through computerized much better, more efficient and effective in generating reports or information required. Keywords: Information Systems, Preorder, Borland Delphi 7.0, Mysql.